Observation of heat pumping effect by radiative shuttling - Li, Yuxuan; Dang, Yongdi; Zhang, Sen; Li, Xinran; Chen, Tianle; Choudhury, Pankaj K.; Jin, Yi; Xu, Jianbin; Ben-Abdallah, Philippe; Ju, Bing-Feng; Ma, Yungui (Nature communications, 2024)
Heat shuttling phenomenon is characterized by the presence of a non-zero heat flow between two bodies without net thermal bias on average. It was initially predicted in the context of nonlinear heat conduction within atomic lattices coupled to two time-oscillating thermostats. Recent theoretical works revealed an analog of this effect for heat exchanges mediated by thermal photons between two solids having a temperature dependent emissivity. In this paper, we present the experimental proof of this effect using systems made with composite materials based on phase change materials. By periodically modulating the temperature of one of two solids we report that the system akin to heat pumping with a controllable heat flow direction. Additionally, we demonstrate the effectiveness of a simultaneous modulation of two temperatures to control both the strength and direction of heat shuttling by exploiting the phase delay between these temperatures. These results show that this effect is promising for an active thermal management of solid-state technology, to cool down solids, to insulate them from their background or to amplify heat exchanges. Authors demonstrate a net heat flux between two objects at averagely zero temperature gradient, exploring the nonlinear thermal emissivity based on phase change materials.